Pengembangan Kompetensi Literasi Digital Pada Guru Untuk Optimalisasi Pembelajaran Jarak Jauh (PJJ) - Nanda Novita; Marhami Marhami; Halimatus Sakdiah; Muliani Muliani (MATAPPA: Jurnal Pengabdian Kepada Masyarakat, 2021)
The purpose of this activity is to improve digital literacy competencies and optimize the ability of teachers to use e-learning media in the implementation of  Distance Learning (PJJ). The training materials are tailored to the needs of teachers as participants to overcome digital literacy problems that exist in schools. The method of implementation is carried out by the lecture method to deliver digital literacy competency material, training methods to provide direct experience in using e-learning applications, and dialogical methods. To measure the increase in participants' knowledge and understanding in this activity, questionnaires were given before and after training. The questionnaire contains tests for testing knowledge and understanding of digital literacy and the use of e-learning applications. Participants in this activity were all teachers of SMPN 2 Dewantara, North Aceh. This activity provides significant benefits of improving understanding of teachers' digital literacy competencies and skills in using e-learning applications that can be used in implementing Distance Learning.